Sphingomonas paucimobilis septicemia in a neonate: A rare case report - Priti Chowdhary; Ritesh Ranjan; Anita Pandey; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2016)
Sphingomonas paucimobilis , a yellow-pigmented, aerobic, glucose nonfermenting, Gram-negative bacilli is a rare cause of human infection. It was first discovered as an infective agent in humans in 1977 and named Pseudomonas paucimobilis. It was renamed as S. paucimobilis in 1990 in accordance with phylogenetic data. S. paucimobilis is an aerobic bacterium found in soil and water; it is a rare cause of healthcare associated infections. S. paucimobilis can cause infections in healthy as well as immunocompromised individuals. At first, its colony looks like Gram-positive bacilli colony, so by mistake it is discarded as contaminants. S. paucimobilis is an emerging pathogen and it should not be discarded as contaminants. Here, we report a case of S. paucimobilis bacteremia in a neonate who presented with respiratory distress.